RANCANG BANGUN SIMULASI TERJADINYA LISTRIK DENGAN SUMBER DAYA SAMPAH BERBASIS MULTIMEDIA (STUDI KASUS : TPST BANTAR GEBANG) - Riki Ruli A. Siregar (Sekolah Tinggi Teknik - PLN, 2016)
Learning or material on processing waste to produce electricity is needed because demand for electricity increases, while uncontrolled trash. Uncontrolled increase in litter causes uncontrolled pollution in the air anyway. Coupled with the fossil fuel emissions that are contributing to pollution and environmental pollution are greatest. Processing environmentally friendly fuels such as waste must be developed. Learning about the waste that exists today only still lacking and is still text-based or in book form. This leads to a lack of public interest to learn the material on waste management. The existence of this application, a solution to these problems. This application is designed in the form of exciting multimedia learning so as to increase public interest in the field of waste management. In addition in the form of multimedia, this application is also easy to operate, because the location and navigation menu uncomplicated. Waste processing in this application refers to the existing landfill gas systems in Power Plant Waste (PLTSa) Bantargebang.